Evaluation of patterns of mandibular bone invasion in CBCT of patients with oral squamous cell carcinoma: A descriptive study - Prashanth Shenoy; P Archana; Laxmikanth Chatra; K M Veena; Rachana V Prabhu; Prathima Shetty (Wolters Kluwer Medknow Publications, 2022)
Background: One of the crucial factors in the pretreatment analysis of patients with oral squamous cell carcinoma (OSCC) is the detection of the presence of bony invasion. This will indicate aggressiveness, and its patterns may also express the conduct of the lesion. The extent of bony invasion by the tumor will alter the treatment planning and increases the morbidity rate and quality of life. Aim: To evaluate the mandibular invasion patterns in cone beam computed tomography (CBCT) of patients with OSCC. Methodology: A total of 31 CBCT images of OSCC involving the mandible with bony invasion were included and assessed for various invasion patterns. Bony invasion is classified into three patterns: erosive, infiltrative, and mixed. Results: Descriptive analysis was carried out to assess the frequency among various bony invasion patterns. Chi-square test was carried out to find significance between the inferior alveolar nerve canal (IANC) involvement among various patterns of OSCC, which found be to be highly significant. Conclusion: Erosive pattern is the common pattern observed and the mixed pattern was the most frequently associated pattern with the IANC involvement.